PROSES REKRUTMEN DAN SELEKSI TENAGA KERJA OLEH HUMAN RESOURCES DEPARTMENT DI SOCIAL PALACE CAFÉ MALANG - Sari, Luh Kompiang; Ni Ketut Murdani; Akbar Michael Arifin (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2024)
In a company, the recruitment and selection process is one of the crucial processes in determining the quality of prospective employees or applicants. There are several processes that must be carried out by the company in recruiting and selecting a number of employees according to their needs. Making a mistake in choosing employees who are not suitable for their field can be one of the factors leading to a decrease in the quality of the company. This poses a challenge for the HRD in every company, including Social Palace Café in Malang. One of the key factors in creating professional employees lies in the recruitment and selection process of prospective employees. This study aims to determine the recruitment and selection process carried out by the HRD at Social Palace Café in Malang. The research method used by the researcher is descriptive method with data collection techniques through interviews, observations, and documentation. The results of this study shows that the recruitment and selection process of employees carried out by the HRD at Social Palace Café in Malang is done in 6 selection stages and 3 recruitment stages.